Malaria In Pregnancy Wad Medani Teaching Hospital Obs & Gyn - Miskeen, Elhadi Ibrahim; Ahmed Mergani, Omer (Gezira Journal of Health Sciences, 2004)
This is a prospective hospital – base study carried out in Wed Medani Teaching Hospital for Obs and Gyn (WMTHOG),during the period from 5 th October 2003 to 30 December 2003. All  pregnant women with malaria admitted to the hospital during that period were included in the study. Malaria was diagnosed by thick and thin blood film, Gemsa's stain. Sever falciparum malaria was diagnosed according to WHO criteria. The national protocol for treatment of malaria with pregnancy was adopted in the management of all women. The results were analysed using SPSS. The total number of pregnant women included in this study were 210. The main results of the study were: (I) severe falciparum malaria 73.4% , (II) anaemia  98.6% of whom 11% was very severe, 20% was severe, (III) hyperparasitaemia 46.7% , (IV) dehydration 33.3% and (V) jaundice 20.5% . Complications on the fetus were: (I) preterm labour 44.1% , (II) low Apgar's score < 7 55.9% , (III) low    weight < 2.5 44.1% and (IV) perinatal death 5.5% . Quinine was the main drugs used. Conclusion: pregnant women admitted to the hospital need intensive care. Although there was no mortality but morbidity was high. The current protocol is adequate in reducing mortality